Subchronic toxicity and possible teratogenic effect in rats of ethanol extract of Chuquiraga spinosa (huamanpinta) - Condorhuamán, Martín (2017)
Objective of this experimental study was to determine the subchronic toxicity and possible teratogenic effect of ethanol extract from Chuquiraga spinosa (huamanpinta) in Holtzman rats. Was used for the determination of subchronic toxicity 60 rats (30 males and 30 females); the first, control, group received saline solution 4 mL/kg and the second group extract at 200 mg/kg during four consecutive months, making evaluation hematological and biochemical the second, third and fourth month. At the end of the trial (fourth month) was made pathological examination. The determination of possible teratogenic effect was performed using 40 female rats and ten male rats. Female rats recived 200 mg/kg daily by a month before mating and until the birth of brood, was evaluated the number implementations to uterine horns level, live and dead fetuses, and external morphological abnormalities of the offspring. The phytochemical study found that the ethanolic extract showed tannins, phenolic compounds, alkaloids, flavonoids and saponins. In the chronic toxicity test was observed that there was significant difference in hematological and biochemical values to second, third and fourth month of treatment and no histopathological changes in liver, kidney and brain. Regarding to possible teratogenic effect was observed no difference in the weight of pregnant rats, number of fetal implantations, number of live fetuses and morphological abnormalities of the offspring at birth even two months follow up. Was concluded that ethanolic sxtract not showed sub-chronic toxicity or teratogenic effect at 200 mg/kg dose.